التفكير ما وراء المعرفي وعلاقته بمستوى الطموح لدى طلبة الجامعة (Comprehensive Journal of Science, 2025)
The present study aims to identify:•         The level of metacognitive thinking and the differences according to gender and academic level among the study sample.•         The level of aspiration among the study sample and the differences according to gender and academic level.•         The nature of the correlational relationship between metacognitive thinking and the level of aspiration among the study sample.The study was limited to students of the Faculty of Information Technology during the Spring 2024 semester, whose total number was (1,320). The study sample consisted of (132) male and female students; (32) questionnaires were excluded due to incomplete responses, resulting in a final sample of (100) participants, including (57) males and (43) females.The Metacognitive Thinking Scale developed by Schraw and Dennison (1994), translated by Al-Jarrah and Ubaidat (2001), and the Level of Aspiration Scale by Kamili Abdulwahid were used in this study. The following statistical methods were applied in data analysis: arithmetic mean, standard deviation, t-test, and correlation coefficient.The results revealed the following:•         The sample participants demonstrated high levels of metacognitive thinking, encompassing “knowledge of cognition, regulation of cognition, and processing of knowledge.”•         A generally high level of aspiration was observed among the sample, with slight variation in some dimensions, such as the tendency toward struggle/perseverance.•         There were no statistically significant differences between males and females in the level of aspiration and metacognitive thinking, except for females’ superiority in the dimension of orientation toward excellence.•         Statistically significant differences were found in favor of first-year students in the level of metacognitive thinking and in some dimensions of the level of aspiration.•         There was a positive, statistically significant correlational relationship between the level of aspiration and metacognitive thinking.